A Study of Two- Dimensional Non Linear Model of Truck Vehicle and its Impact on Determining the Maximum Speed of Driver Comfort - Salim Y. Kasim; Raaid M. Hameed (Tikrit Journal of Engineering Sciences, 2018)
Ride comfort is one of the important requirement which cars manufactures is try to achieved it because its directly effect on the sales rate, so it was to be tacking the factors that effect on the comfort degree of car users , in this field it has been concentrating on the driver comfort because of his responsibility on the car drive and on passengers safety as well as to focus on the road and see the obstacles, this is achieved by isolating the vehicle body from the vibrations results due to irregularly by use suitable suspension system . In order to obtain accurate results, we study the non – linear disposition of system parts by taking into account the most prominent source of non-linearity represented by large angle of swing and non-linearity of spring and damper behavior, appropriate model was chosen by taking non-linear half truck vehicle model with four degree of freedom and by considering rigid vehicle body using two types of excitation half sin wave and trapezoidal obstacles as an expression of road irregularly. A Fortran computer program for simulation the results represented by displacement, velocity and acceleration in the center of gravity of vehicle body (C.G) , then comparison with recently published research was doing and it shown an acceptable compliance degree, to find out the improvement extent when taking into account the system non – linearity we compare with linear halve truck vehicle model and found that the adopting of non – linearity leads to improve the results, then an investigation to the driver comfort subject been carried out to know what we have achieved in this field by choose Ride Comfort Level (RCL) as comfortable criteria then the results have been used to determine the maximum speed that keeps the vehicle within comfort limit using three types of obstacles . It was found that the adopting of non-linearity in the accounts gives more speed range. Thus it can be say that we have achieved the goal of this research.